ANALISIS FAKTOR EKONOMI PENYEBAB ANAK PUTUS SEKOLAH JENJANG PENDIDIKAN MENENGAH DI DESA TELUK KEMBANG - Ziana, U.; Aminuyati, Aminuyati; Khosmas, F. Y. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractIn Teluk Kembang village The majority of the population work as rubber farmers, but the fact shows not all rubber farmers live in better condition, many of them are less capable because of the income of rubber farmers And the many daily necessities that must be met. The low income of people with rubber farmers makes parents difficult to get their children to a higher level. And so does the environment that greatly affects children dropouts. The research method used is qualitative descriptive. The research venue is held in Teluk Kembang village. The children of school dropouts and parents are experiencing dropouts. The factors that cause dropout children are the family economic factors, family factors, environmental factors. The most dominant factor of the cause of dropout children is the family economic factor. Most of the people in Teluk Kembang village work as a rubber pengrake which is very cheap and the income is only enough to provide daily needs. The price of rubber per kg is Rp. 6,000, 00 and the average monthly income is Rp. 500.000, 00-Rp. 1,100,000 while the monthly expenditure is RP. 700,000, 00-Rp. 1.050.000, 00. Parents ' efforts to overcome dropouts are by observing children's learning activities so that children are not negligent with the lesson.Â Keywords: School dropouts, family economic factors, rubber farmers